Financial Sustainability of Waste Management Service: A Case Study of Pokhara Sub-Municipal Corporation - Baral, Keshar J (Journal of Political Science, 2004)
Using the data set provided in the Cost Recovery System of the Waste Management System of Pokhara Sub-municipal Corporation (PSMC), the financial sustainability of the proposed waste management has been examined in this article. Financial sustainability indicators-operating cost ratio and cash operating ratio-show that the proposed system is financially sustainable provided that PSMC imposes the tourist fee and uses the revenue raised from the tourist fee to run the sanitary landfill site, build up the necessary institutional arrangement and capability required to run the designed system and recover the operation cost from the users. Journal of Political Science Vol.7(1) 2004 p.5-14